Spatial control of the gap gene knirps in the Drosophila embryo by posterior morphogen system. - Pankratz, M.J.; Busch, M.; Hoch, M.; Seifert, E.; Jäckle, H. (Science, 1992)
The gap genes of Drosophila are the first zygotic genes to respond to the maternal positional signals and establish the body pattern along the anterior-posterior axis. The gap gene knirps, required for patterning in the posterior region of the embryo, can be activated throughout the wild-type embryo and is normally repressed from the anterior and posterior sides. These results provide direct molecular evidence that the posterior morphogen system interacts in a fundamentally different manner than do hunchback and bicoid, which are responsible for anterior pattern formation.